High Dose Oestrogen in Life Threatening Obscure Gastrointestinal Bleeding - Meng Kang Tee; Khairul Najmi Muhammad Nawawi; Chai Soon Ngiu; Deborah Chew Chia Hsin; Raja Affendi Raja Ali; Zhiqin Wong (Interna Publishing, 2022)
Obscure gastrointestinal bleeding is defined as recurrent or persistent gastrointestinal bleeding in the setting of normal upper and lower endoscopies. There are reported use of numerous pharmacological agents to halt the bleeding, including oestrogen. We report a case of middle age gentleman with multiple comorbidities, presented with life threatening gastrointestinal bleeding. He underwent bidirectional endoscopies and mesenteric angiogram, but failed to localise the bleeding. Red blood cell scintigraphy showed numerous bleeding points in small and large bowels. A 5-day oral high dose oestrogen was prescribed in view of difficulty to manage the bleeding, in which the hemostasis was ultimately achieved.